Personal Branding on Social Media: The Role of Influencers - Vasconcelos, Liliana; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
This research paper aims to establish a connection between the concept of Personal Branding and Social Media, understanding how in the 21st-century people do their personal branding through Social Media, taking into account the role of Digital Influencers on Instagram. It is to be expected that these individuals, given their social status, make good personal branding. The methodology approach used was a qualitative one, developed through an interview with 25 questions and counting with 10 responses, half woman, and half male. The interviewees were Portuguese Instagram Influencers. Some conclusions that were possible to draw were that becoming an Influencer is something well thought, people do intentional personal branding, they often plan their content, consider the impact of their actions on others, the number of followers is important when addresses to job opportunities. In the perspective on how Influencers build that online presence, the main factors mentioned are consistency, authenticity/genuineness, and interaction with the audience.